Facial diplegia, a possible atypical variant of Guillain-Barré Syndrome as a rare neurological complication of SARS-CoV-2 - Juliao Caamaño, David Salomón; Alonso Beato, Rubén (Journal of clinical neuroscience, 2020)
•Neurological complications related to SARS-CoV-2 are being reported around the world.•The more “rare” cases reported, causality and strong conclusions can be established.•Facial Diplegia and Guillain-Barré Syndrome have been connected to SARS-CoV-2 twice. We present a case of facial diplegia after 10 days of SARS-CoV-2 confirmed infection symptoms in a 61 year old patient without prior clinically relevant background. There are few known cases of Guillain-Barré Syndrome (GBS) related to SARS-CoV-2 infection; we propose this case as a rare variant of GBS in COVID-19 infection context, due to Its chronology, clinical manifestations and cerebrospinal fluid (CSF) findings.